The Influence of Financial Literacy, Lifestyle and Self Control on Consumptive Behavior of Management Study Program Students, Faculty of Economics and Business Universitas Muhammadiyah Sumatera utara - Ade Gunawan (International Journal Reglement & Society (IJRS), 2023)
This study aims to determine the effect of Financial Literacy on the Consumptive Behavior of Muhammadiyah University Students in North Sumatra, the Management Department of the Faculty of Economics and Business. To determine the effect of Lifestyle on Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. To determine the effect of Self Control on Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. To determine the effect of Financial Literacy, Lifestyle and Self Control on the Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. The results of this study concluded that partially there is a significant influence of the Financial Literacy variable on the Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. The results of this study concluded that partially there is a significant influence of the Lifestyle variable on the Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. The results of this study concluded that partially there is a significant influence of the Self Control variable on the Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business. The results of this study concluded that simultaneously and significantly there is influence of Financial Literacy, Lifestyle and Self Control on the Consumptive Behavior of Muhammadiyah University Students, North Sumatra, Department of Management, Faculty of Economics and Business.